Assessing Salesperson Performance through Selling Capability and Experience - Sirait, Johanes Christanto Hasian; Ismail, Taufiq (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This study aims to examine the effect of Adaptive Selling Capability, Customer Networking Capability, and Sales Experience on Salesperson Performance. Employing a quantitative approach, the study involved 73 salespersons from Project ABC at PT. XYZ was selected through census sampling. Primary data were collected via questionnaires and analyzed using SPSS version 26. The findings reveal that all three independent variables significantly and positively affect salesperson performance. This suggests that greater adaptability in sales approaches, stronger customer networking capabilities, and broader sales experience contribute to enhanced performance. This research offers valuable insights for companies aiming to improve their sales force and contributes to the body of knowledge in sales management, particularly in the B2B pharmaceutical industry context.